Relationship Between Social Capital and Unemployment Anxiety: An Application on Last Class Students at Ataturk University Faculty of Economics and Administrative Sciences - Ahmet Güney; Elif Çelik (İstanbul İktisat Dergisi)
Unemployment is one of the most important socio-economic problems waiting to be solved in Turkey as in most countries. It is known that unemployment creates economic, psychological and social effects on individuals. One of the most important impacts of unemployment on individuals is unemployment anxiety. Unemployment has a significant place in desperation of future and anxiety of unemployment of individuals aged 15-24. It is thought that membership of an NonGovernmental Organizations, social support from the environmental and social capital will reduce the unemployment anxiety on individuals. In this study, it has been analyzed whether there is a significant relationship between the social capitals and unemployment concerns of university senior students or not. In the study which was applied on the senior students of Atatürk University Faculty of Economics and Administrative Sciences, the existence of the relationship between these two variables was revealed by correlation analysis. The analysis was performed on the responses received from 155 participants who were found to be eligible for the study. As a result of the study, it is showed that there is a negative relationship between social capital and unemployment anxiety, furthermore individuals with high social capital levels decrease their unemployment anxiety. In terms of gender; the level unemployment concerns were higher among women, while in males, the level of social capital was higher. It was concluded that increasing social capital levels of individuals would reduce unemployment concerns and would look more hopeful to the future in this direction.